Analysis of influential factors in laparoscopic myomectomy and estimation of hidden blood loss - Lu, Jingjing; Chu, Lili; Shen, Liliang (Frontiers in Surgery, 2025)
BackgroundHidden blood loss (HBL) is a critical but understudied component of perioperative blood loss in laparoscopic myomectomy, with limited data on its magnitude and associated factors. This study aimed to quantify HBL and identify its influential factors to optimize perioperative blood management and enhance patient recovery.MethodsA retrospective analysis was conducted on 139 patients who underwent laparoscopic myomectomy at The Affiliated People's Hospital of Ningbo University between January 2022 and December 2023. Demographic, surgical, and laboratory data were collected. HBL was calculated using validated formulas (Nadler, Gross, and Sehat). Univariate analyses (Kruskal–Wallis test, Pearson correlation) and multivariate linear regression were performed to identify factors associated with HBL, with statistical significance set at p < 0.05.ResultsThe mean HBL was 0.33 ± 0.02 L, accounting for 86.34% of total blood loss (TBL). Univariate analysis showed HBL was significantly associated with the number of removed fibroids (r = 0.172, p < 0.05) and their total volume (r = 0.202, p < 0.05). Multivariate regression confirmed these as independent predictors (total volume: β = 0.002, p = 0.002; number: β = 0.172, p = 0.006). Additionally, surgeon experience and senior assistants were associated with shorter operative time (p < 0.05), which correlated with lower hospitalization costs (r = 0.387, p < 0.001).ConclusionHBL constitutes a substantial proportion (86.3%) of TBL in laparoscopic myomectomy, with fibroid number and total volume as key independent predictors. Optimizing surgical efficiency through experienced teams and reducing fibroid burden may help mitigate HBL and lower hospitalization costs, informing perioperative management strategies.